Benefits of Providing Feedback and Utilisation Metrics to Specialists on Their Participation in eConsult. Issue 1 (31st December 2022) - Keely, Erin; Mitchell, Rhea; Guglani, Sheena; Archibald, Douglas; Afkham, Amir; Liddy, Clare
ABSTRACT: Our study evaluates the impact of feedback sent to specialists participating in eConsult services. eConsult Specialists from two eConsult services in Ontario, Canada, received feedback on their use of eConsult via bi-annual specialist reports. An 11-item survey was developed to evaluate the impact, content, and distribution process of these specialist reports. We distributed 742 specialist reports in March 2021 and surveyed the specialists in July 2021. Our findings show that specialists largely felt that the feedback received validated their efforts (83%) and that receiving the report made them more likely to continue to participate in the eConsult service (59%). Most did not feel judged (74%) or distressed (79%) by the reports, and 72% said that reporting the median self-reported billing time did not impact their own billing times. Overall, eConsult services can capture, report and aggregate data valuable to specialists and is useful for Continuing Professional Development. Benefits and lack of risk implementing this type of feedback should encourage other services to consider similar processes.